Archaeological and ethnographic evidence of domination in indigenous Latin America - Chacon, Yamilette; Chacon, Richard J., 1959- (University Press of Florida, 2023)
"This volume explores the nature of power relations and social control in Indigenous societies of Latin America as reflected in archaeological, osteological, and ethnohistorical records"--